Apakah Kinerja Lingkungan Mempengaruhi Pengungkapan Lingkungan? - Widyawati Widyawati; Pancawati Hardiningsih (Jurnal Akuntansi dan Pajak, 2022)
Environmental disclosure is one of the company's communications on environmental performance information to all its stakeholders. Environmental disclosure has become a mandatory reporting item that has been regulated in government regulations but in practice there are still many companies that do not disclose the environment. This study aims to empirically examine the effect of environmental performance on environmental disclosure. Environmental disclosure standards use the Global Reporting Initiative (GRI) index as a benchmark and analysis of annual reports and sustainability reports. The selected sample is 96 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period. The sampling technique used purposive sampling and the data were analyzed using multiple linear regression. The results showed that environmental performance had an effect on environmental disclosure.